Community Disaster Vulnerability - Zakour, Michael J. author. aut Link
VIII, 180 p.
Keywords: Large-scale disasters--Hurricane Katrina, the 2004 tsunami, the BP oil spill--are enduring reminders of the fragility of our natural resources, our built environment, and our human communities. Particularly apparent is how much longer recovery takes for some survivors than others--and that some never recover at all. Community Disaster Vulnerability offers a deeply nuanced understanding of how disasters affect at-risk populations such as the poor and the elderly, beginning with factors that contribute to disaster risk. Its focus on the complex layers of disruption caused by disasters links research findings across disciplines and levels of intervention. Concepts and models are included that systematically explain the sociopolitical aspects of disasters and identify relevant interventions for bolstering community resilience, providing social support, and distributing post-disaster resources. These practical applications of the theory propose methods of proactive planning for and responses to natural, manmade, or hybrid crises. This far-reaching volume: Introduces a general framework for disaster vulnerability theory. Explains social development and resilience perspectives as they relate to vulnerability theory. Illustrates the use of geographic methods in describing the locations, depth, and extent of disaster vulnerability. Examines cross-sectional research designs and linear statistical models in community disaster vulnerability research. Applies a system dynamics simulation model to disaster policy and planning. Features a detailed model of vulnerability and resilience factors in disasters. Skillfully blending analysis, empathy, and practicality, Community Disaster Vulnerability will advance the work of human service personnel, emergency managers, and professionals in social work education and research.